INTEGRASI KURIKULUM DAN PENDIDIKAN KARAKTER MELALUI EKSTRAKURIKULER TAHFIDZ DI SD MUHAMMADIYAH PAKEL YOGYAKARTA - Pratama, Vinda Ayu; Dhiniaty Gularso (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the process of integrating curriculum and character education through tahfidz extracurricular activities at SD Muhammadiyah Pakel Yogyakarta. The research is driven by the increasing need to strengthen students' moral and spiritual values amidst the challenges of modern education. The tahfidz program, as an Islamic-based extracurricular activity, is not only intended to enhance Quran memorization skills but also to instill noble values such as discipline, honesty, and responsibility. The research approach used is descriptive quantitative, with data collection techniques through interviews, observation, and documentation. Data analysis uses the interactive model of Miles and Huberman, which includes data reduction, data presentation, and drawing conclusions. The results of the study indicate that curriculum integration occurs through three main stages: (1) planning, namely aligning the tahfidz program with the school curriculum and character values (2) implementation, carried out through routine activities such as Dhuha prayer and reviewing as well as memorization using the talaqqi method. (3) evaluation, assessing memorization ability and changes in attitude regarding discipline, responsibility, and religious behavior. Supporting factors of the program include teacher commitment, while inhibiting factors are time limitations and variations in students' memorization abilities. Tahfidz activities have been proven to enhance students' religious character and responsibility, and serve as a strategic means of combining formal curriculum objectives with character education in schools.